Pengaruh Aspek Sosial Budaya Pada Badan Usaha Milik Desa Maju Bersama Desa Wolotolo, Kabupaten Ende, Nusa Tenggara Timur - Raymundus Lullus Rua Raki (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The article entitled The Influence of Socio-Cultural Aspects on Village-Owned Enterprises (BUMDes) Maju Bersama Wolotolo Village, Ende Regency, East Nusa Tenggara aims to examine the influence of social and cultural aspects in the formation, participation or selection of business units, as well as the recruitment of BUMDes members between 2016-2017.The focus of this research is to see how customs, traditions and cultural values become the basis and influence the formation process of BUMDes. This research utilizes Structural Functionalism and Social Capital theories. A qualitative approach is used in this research to collect and analyze data. Data were collected through interviews, observation and documentation. Based on the research, it was concluded that the traditions and customs of the local community influenced the pattern of cooperation based on the tradition of gathering together in the village, the recruitment of administrators who were influenced by customs based on closeness and kinship factors, and the pattern of work that was strongly influenced by the development of local community habits to be very fund-oriented. This then brings positive impacts such as loyalty, but on the other hand there are also many negative impacts such as the low professionalism, skills and capacity of the management, the exclusion of other parties from the management of the BUMDes, as well as making a work pattern that always sees the availability of funds as a benchmark for organizing activities so that all of that leads to the stagnation of business activities in the BUMDes.